Pengaruh Semangat Kerja, Disiplin Kerja dan Budaya Kerja Terhadap Produktivitas Kerja Pada PT Arina Parama Jaya Gresik - Ibrahim Zakariya; Roziana Ainul Hidayati (Universitas Nusantara PGRI Kediri, 2024)
Value fluctuations arrive late and arrive on time so this has the potential to disrupt work productivity. Another factor faced by PT. Arina Parama Jaya is a decline in employee morale in achieving predetermined targets. There is a tendency for some employees to be lazy and come late and take the tasks given to them for granted. The impact of this behavior cannot be underestimated, as it includes more than just reduced productivity. This can also affect the company's image, because a company's reputation is formed from the quality of service and commitment to excellence. This research uses a quantitative type of research. The population and sample are all 104 employees. The data analysis technique for this research uses the PLS (Partial Least Square) analysis method with the help of the SmartPLS version 4.0 application. PLS. The research results can be concluded that work enthusiasm, work discipline and work culture have a significant positive influence on employee work productivity. High morale motivates employees to give their best in their work, while good work discipline helps increase efficiency and reduce the level of negligence. A positive work culture creates an environment that supports and encourages employees to contribute optimally.